A novel approach to friction drilling process: experimental and numerical study on friction drill joining of dissimilar materials AISI304/AL6061 - Dehghan, Shayan; Abbasi, Rasol; Baharudin, B. T. Hang. Tuah b.; Mousavi, Mohsen Loh; Soury, Ehsan (Multidisciplinary Digital Publishing Institute, 2022)
Joining dissimilar materials is always a challenging and interesting topic for researchers and industries. Friction drill joining, as a solid-state process, is a novel approach to connecting similar and dissimilar materials. Dissimilar metals, especially ultra-high-strength steels and aluminum alloys, are used significantly for the mass reduction of automotive bodies, and to reduce CO2 emissions in the automotive industry. In the current work, a friction drill joining technique for joining AISI304 and Al6061 was experimentally and numerically studied. A technique for improving joint strength, load-clamping modification, and tool movement was also introduced. The required thrust force is measured, and it is proven that adding sheet layers does not significantly affect the required thrust force. To understand and identify the mechanism of the process, and its material behaviour, material stirring and formation in the joint region were analyzed. A thermo-mechanical finite element model was also developed, and the thermal stress, plastic strain, and temperature were studied. A numerical comparison between joints formed under normal and improvement conditions was conducted, and the significant effect of the improvement conditions on joint strength and formed-bush quality was found. Based on the findings, the great potential of using friction drill joining for joining dissimilar materials is confirmed.